Power convexity of a class of Hessian equations in the ball - Ye, Yunhua (Global Journal of Mathematical Analysis, 2015)
Power convexities of a class of Hessian equations are considered in this paper. It is proved that some power functions of the smooth admissible solutions to the Hessian equations are strictly convex in the ball. For a special case of the equation, a lower bound principal curvature and Gaussian curvature estimates are given.